2019
DOI: 10.1063/1.5064545
|View full text |Cite
|
Sign up to set email alerts
|

Pair and many-body interactions between ligated Au nanoparticles

Abstract: We report the results of molecular dynamics simulations of the properties of a pseudo-atom model of dodecane thiol ligated 5-nm diameter gold nanoparticles (AuNP) in vacuum as a function of ligand coverage and particle separation in three state of aggregation, namely the isolated AuNP, isolated pair of AuNPs and a square assembly of AuNPs. Our calculations show that the ligand density along a radius emanating from the core of an isolated AuNP has the same gross features for all values of the coverage; it oscil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 73 publications
1
27
0
Order By: Relevance
“…As noted above, while there may be additional contributions to this simple approximation, such thermodynamic parameters are small enough so as to not significantly affect the conclusions drawn here, and these assumptions should hold for systems like the NCTs that possess long ligands and directional enthalpic interactions. 27,28 Based on these thermodynamic parameters, a "bundle bond" therefore represents a collection of DAP and Thy groups where the entropy penalty for linking any given pair of polymer chains comprising that bundle is less than the strength of the DAP-Thy Figure 3. Thermodynamics of bundle bond formation are controlled via nanoscale design handles.…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, while there may be additional contributions to this simple approximation, such thermodynamic parameters are small enough so as to not significantly affect the conclusions drawn here, and these assumptions should hold for systems like the NCTs that possess long ligands and directional enthalpic interactions. 27,28 Based on these thermodynamic parameters, a "bundle bond" therefore represents a collection of DAP and Thy groups where the entropy penalty for linking any given pair of polymer chains comprising that bundle is less than the strength of the DAP-Thy Figure 3. Thermodynamics of bundle bond formation are controlled via nanoscale design handles.…”
Section: Resultsmentioning
confidence: 99%
“…These effective interactions are computed from fully atomistic molecular simulations of nanoparticles. In this regard there have been a number of studies previously reported [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] that have computed effective inter-particle interactions. These studies looked at various aspects of interactions between nanoparticles including length of ligand chains, role of solvent, three-body interactions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These fits to two and three body interactions should satisfy the general features of interactions between surfactant coated nanoparticles in a good solvent. Liepold et al 25 have given a detailed overview of these features of nanoparticle interactions and some of the important observations are given below.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Many-body effective interactions involving three or four nanoparticles can also be significant. 19,20 These potentials could then be used in more coarse-grained models, treating the polymer as an implicit medium. When the aim is to obtain qualitative insights, it is generally more useful to adopt from the outset a coarse-grained model for 2 This is the author's peer reviewed, accepted manuscript.…”
Section: Introductionmentioning
confidence: 99%